Efficient anonymous reputation-based revocation without TTP - Li XI; ENGDeng-guo F (Tongxin xuebao)
The security problems in PE(AR)2are pointed out then a new TTP-free scheme is proposed to supports anony-mous reputation-based revocation. This scheme allows the SP(service provider) to assign positive or negative scores to anonymous sessions and block users whose reputations are not high enough. The benchmark shows that for proposed scheme the SP can handle 820 authentications per minute while PERM can only handle 21 authentications per minute.